Multiple epidermal cysts on regressing hemangioma. - Bonifazi, E.; Garofalo, L. (European Journal of Pediatric Dermatology, 2010)
Case report. A 3-month-old girl presented a voluminous hemangioma of the right subscapular region, so we decided to wait for its spontaneous regression. At the age of 3 only its deep component remained. On its surface and only on it there were about ten dilated hair follicles filled with keratin (Fig. 1). One of them presented suppurative inflammation and her mother told us about periodic inflammation affecting always the perifollicular region, unresponsive to antibiotic therapy. At the age of 6 (Fig. 2) the situation was unchanged. We visited again the patient at the age of 21 (Fig. 3). Hemangioma had completely regressed, with thin and dystrophic skin. Small areas of atrophic scarring and some comedo cysts (Fig. 3, rectangle down on the left), clearly visible dermoscopically (Fig. 4) were also observed. The final diagnosis was multiple epidermal cysts on residua of hemangioma.